Analyzing domestic & foreign banks performance using camel approach - Lee, Mary Pik Yuan (Faculty of Economics and Business, 2012)
~s banking sector is considered as one of the fastest growing sector, it plays a vital role in the economic development. Apparently, banks are the main stimulus of the economic progress of a country. On 6th May, 2011, after the merger of EON Capital and Hong Leong Bank Berhad, Bank Negara Malaysia expects more consolidation among the domestic banks and financial institutions as the banking sector continues to liberalise.(WWW.bnm.g~v.m~ Capital Adequacy, Asset Quality, Management Quality, Earning Quality and Liquidity (CAMEL) Model in banking sector has been improved over the earlier years in terms of focus and can detennine how well the financial institutions can manage banks perfonnance. An attempt in this present study is to evaluate domestic and foreign banks performance using CAMEL approach. The findings provides empirical support of relationship between the ratios and banks performance. The model for this study is adopted from Ilhomovich (2009) who has tested on Malaysian banks. It is found that more prudent indicators like gross domestic products, earnings before interest, amortization and loan loss provision are some ofthe recommendations arising from this research .